The Mediating Role of Perceived Value in the Effects of Trust and Perceived Quality on Customer Satisfaction and Repurchase Intention Among Life Insurance Policyholders - Farras Ramadhan (Publikasi Indonesia, 2026)
Increasing competition in Indonesia's life insurance industry has intensified the need for companies to retain policyholders and strengthen repurchase intention through trust, service quality, perceived value, and customer satisfaction. This study aims to analyze the effects of trust and perceived quality on customer satisfaction and repurchase intention, with perceived value as a mediating variable, among life insurance policyholders in Indonesia. A quantitative approach was applied using an online survey distributed to 240 active life insurance customers from leading brands, including AXA Mandiri, Allianz, Prudential, AIA, BNI Life, Manulife, ACA Insurance, and BRI Life. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS. The results show that trust positively and significantly affects perceived quality, perceived value, customer satisfaction, and repurchase intention. Perceived quality significantly influences perceived value and repurchase intention, but does not directly affect customer satisfaction. Perceived value and customer satisfaction significantly enhance repurchase intention, while perceived value mediates the relationship between trust and repurchase intention, as well as between perceived quality and customer satisfaction. In conclusion, perceived value is a crucial mechanism in strengthening customer satisfaction and repurchase intention, while trust remains the foundation of long-term customer relationships in life insurance services.